2012
DOI: 10.1007/978-3-642-29627-7_35
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Whole Genome Realignment Reveals Many Novel Non-coding RNAs

Abstract: Recent genome-wide computational screens that search for conservation of RNA secondary structure in whole-genome alignments (WGAs) have predicted thousands of structural noncoding RNAs (ncRNAs). The sensitivity of such approaches, however, is limited, due to their reliance on sequence-based whole-genome aligners, which regularly misalign structural ncRNAs. This suggests that many more structural ncRNAs may remain undetected. Structure-based alignment, which could increase the sensitivity, has been prohibitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Recently, Will et al [10] reported many novel ncRNAs using structured-based whole genome realignment. In their method, existing whole genome sequence alignment was used as the base alignment.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Will et al [10] reported many novel ncRNAs using structured-based whole genome realignment. In their method, existing whole genome sequence alignment was used as the base alignment.…”
Section: Related Workmentioning
confidence: 99%
“…The idea of banded alignment has been used in both sequence alignment and structural alignment programs [9,10,11,12,13]. By applying dynamic programming in banded search space, the running time complexity of alignment programs can be reduced.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Because recent studies have suggested that re-alignment of genome sequence alignments reveals new non-coding RNAs [19], this function will be useful.…”
Section: Introductionmentioning
confidence: 99%